Three-Dimensional Simulation Platform for Optimal Designs of the MEMS Microphone - Cai, Jianbing; Zhou, Jian; Ji, Zhangbin; Tan, Kaitao; Liu, Yi; Fu, Yongqing (Frontiers in Materials, 2022)
MEMS microphone has a wide range of application prospects in electronic devices such as mobile phones, headphones, and hearing aids due to its small size, low cost, and reliable performance. Research and development of MEMS microphones involves multiple thermo-electro-mechanical couplings among various physical and electrical fields. Unfortunately, there is not an accurate three-dimensional (3D) MEMS microphone simulation platform, which can be applied for the design of chip parameters and packaging characteristics. Herein, based on commercial COMSOL software, we have established a 3D simulation platform for MEMS microphones, which is used to systematically study the influences of geometric structure and physics parameters on the sensitivity and frequency responses of the microphone and consider the influences of packaging characteristics on the performance of the microphone. The simulation results are consistent with those obtained using a lumped element method, which proves the accuracy of the simulation platform. The platform can be used to design and explore new principles or mechanisms of MEMS microphone devices.